A very rare pathogen in peritoneal dialysis peritonitis: Serratia liquefaciens - Ozant Helvaci (Saudi Journal of Kidney Diseases and Transplantation, 2019)
Peritoneal dialysis (PD) peritonitis has been decreasing in frequency in recent years. However, it still causes significant morbidity and mortality. Nearly 1%–6% of all peritonitis attacks result in death. Hospitalizations, loss of PD access, and intravascular catheter insertion for hemodialysis are some examples of morbidity. Approximately 15%–20% of the infectious mortality of PD patients is attributed to peritonitis. The responsible pathogens are usually Gram-positive bacteria, but unusual pathogens may be present. Prognosis is worse when Gram-negative and fungal pathogens are involved. We report a case of Serratia liquefaciens peritonitis due to defiance of hygienic practices which presented with severe abdominal pain and fever and led to loss of PD access.